Additional mutations in SRSF2, ASXL1 and/or RUNX1 identify a high-risk group of patients with KIT D816V+ advanced systemic mastocytosis - Jawhar, Mohamad; Schwaab, Juliana; Metzgeroth, Georgia; Kluger, Sebastian; Naumann, Nicole; Hofmann, Wolf-Karsten; Fabarius, Alice; Reiter, Andreas (Leukemia, 2016)
Most patients with KIT D816V+ advanced systemic mastocytosis (SM) are characterized by somatic mutations in additional genes. We sought to clarify the prognostic impact of such mutations. Genotype and clinical characteristics of 70 multi-mutated KIT D816V+ advanced SM patients were included in univariate and multivariate analyses. The most frequently identified mutated genes were TET2 (n=33 of 70 patients), SRSF2 (n=30), ASXL1 (n=20), RUNX1 (n=16) and JAK2 (n=11). In univariate analysis, overall survival (OS) was adversely influenced by mutations in SRSF2 (P<0.0001), ASXL1 (P=0.002) and RUNX1 (P=0.03), but was not influenced by mutations in TET2 or JAK2. In multivariate analysis, SRSF2 and ASXL1 remained the most predictive adverse indicators concerning OS. Furthermore, we found that inferior OS and adverse clinical characteristics were significantly influenced by the number of mutated genes in the SRSF2/ASXL1/RUNX1 (S/A/R) panel (P<0.0001). In conclusion, the presence and number of mutated genes within the S/A/R panel are adversely associated with advanced disease and poor survival in KIT D816V+ SM. On the basis of these findings, inclusion of molecular markers should be considered in upcoming prognostic scoring systems for patients with SM.